Mineralogical and geochemical characteristics of Triassic lithium-rich K-bentonite deposits in Xiejiacao section, South China - Lin, Yongjie (2020)
Widespread alteration in the Early–Middle Triassic volcanic ash of the Xiejiacao section, south China, has resulted in significant occurrences of lithium-rich K-bentonite deposits with economic potential. Detailed mineralogical and geochemical investigations of Li-rich K-bentonite deposits from the Xiejiacao section of Guangan city, South China, are presented here. The X-ray diffraction (XRD) data and major element chemistry indicates that the Li-rich K-bentonite deposits contain quartz, clay minerals, feldspar, calcite and dolomite, and the clay minerals are dominated by illite and ordered (R3) illite/smectite (I/S). The concentrations of major and trace elements in Li-rich K-bentonite deposits altered from volcanic ashes are most likely derived from felsic magmas, associated with intense volcanic arc activity. The composition of the clay components suggests that the Li-rich K-bentonite deposits are probably altered from the smectite during diagenesis, whereas smectite is mainly formed by submarine alterations of volcanic materials and subsequently the I/S derived from the volcanogenic smectite illitization. Moreover, accurate determination of the structure in I/S reveals that the temperatures reached by the sedimentary series are around 180 °C with a burial depth of ~6000 m. The widely distributed lithium-rich clay deposits strongly indicate widespread eruptions of volcanic ashes in the Early–Middle Triassic, which released huge amounts of volcanic ash. Lithium fixed in the illite and I/S is considered to have leached from the volcanogenic products by a mixed fluid source (i.e., meteoric, porewater and hydrothermal fluids). These Li-rich clay minerals in the marine basin contain economically extractable levels of metal and are a promising new target for lithium exploration.